Implementation of Humanistic Islamic Education Management in Developing the Morals and Character of Students - Siti Nur Fikriyah; Kartimi Kartimi; Imam Subasman; Abdul Karim; Vasavvi Acharjya; Nur Muhammad Iskandar (Sakura Digital Nusantara, 2026)
Purpose: This study examines the implementation of humanistic Islamic education management in supporting students’ moral and character development in a contemporary elementary madrasah context, where character education is often implemented separately from management practices. Method: This research uses a qualitative case study approach conducted at Al Umm Elementary Madrasah, Klari District. Data were collected through semi-structured interviews with the principal and teachers, classroom observations, and school documentation. Data analysis followed thematic analysis to identify patterns in management practices related to character education. Findings: The findings indicate that humanistic Islamic education management is reflected in participatory leadership practices, integration of Islamic values in classroom activities, and the development of a school culture that emphasizes discipline, empathy, and responsibility. However, the implementation is context-dependent and varies across school activities, particularly in classroom practices and extracurricular programs. The role of the principal and teachers is important in modeling values, although its consistency is influenced by situational factors. Research Implication: The study suggests that humanistic-oriented management can support character education when integrated into daily school practices. However, its effectiveness depends on sustained leadership commitment and teacher involvement in implementing values-based education. Originality: Rather than proposing a generalizable model, this study provides a contextual description of how humanistic Islamic values are practiced in school management at a specific madrasah, contributing empirical insight into the integration of character education within management practices in a local setting.